HPLC Estimation of Mangiferin in Salacia chinensis Linn. - SHASTRY, VIJAYA; HALDANKAR, ASHISH; KADAM, NITIN (Asian Journal of Chemistry, 2010)
A selective and reliable quantitative high performance liquid chromatographic method has been developed and validated for the determination of mangiferin from Salacia chinensis Linn. The detection and quantitation limits were 2.55 and 7.55 μg mL-1, respectively, while the linear range of detection was between 7.55 to 255 μg mL-1.